Temperature and Freshwater Fluxes by Individual Eddies in the North Atlantic Ocean - Müller, Vasco (Universität Bremen, 2017)
This study investigates the temperature and freshwater fluxes by individual eddies in the North Atlantic between 40 degrees-55 degrees N and 60 degrees-10 degrees W for the period January 1993 to April 2014. Focus is on a zonal section along 47 degrees N, roughly at the boundary between the subpolar and the subtropical gyres. The main question is to what extent eddies are responsible for the variability and mixing in the region and how the anomalies of temperature and freshwater carried by eddies contribute to the overall fluxes across 47 degrees N. Almost 37000 eddies with a lifetime longer than one week are detected from surface geostrophic velocity fields derived from satellite-altimetry. First, only surface temperature fluxes based on collocating detected eddies with sea surface temperature observations from satellites are analyzed. The results are compared to two model simulations spanning the period from 2002 to 2013 with different horizontal resolution (1/4 degree and 1/12 degree), allowing to assess the impact of different resolution on the results. The analysis is then extended to three dimensional temperature and freshwater fluxes. The temperature and salinity fields used for the calculation of the fluxes stem from a new product that was derived from dynamic height using the Gravest Empirical Mode (GEM) technique. Using this new product allows for the first time to relate every detected eddy to profiles of temperature and freshwater and to analyze the respective fluxes across 47 degrees N. Since the 1/12 degree model configuration shows the more realistic results for the surface temperature fluxes, the comparison of the observed temperature and freshwater fluxes is confined to this configuration. The highest number of eddies is found along the pathway of the North Atlantic Current (NAC), roughly following the 4000 m isobath, and on the Grand Banks of Newfoundland. The typical vertical extent is around 1400 m, with anti-cyclonic eddies on average 200 m deeper than cyclonic eddies. Relating the observed ...